KOMUNIKASI ANTARBUDAYA JAWA DAN BUGIS DALAM PROSES AKULTURASI DALAM PERKAWINAN DI DESA KOTABARU SEBERIDA KECAMATAN KERITANG INDRAGIRI HILIR PROVINSI RIAU - Selviana Utami; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Javanese and Bugi ethnic marriages are intercultural marriages with different cultural backgrounds. In this marriage, the Javanese follow the Bugis culture in their interactions and customs. However, it takes nothing away from Javanese culture. For this reason, the researchers are interested in knowing the communication between the Javanese and Bugi ethnic groups in the process of acculturation of internal customs and in knowing the communication between the Javanese and Bugi ethnic groups in the process of linguistic acculturation.                    The approach used in qualitative research. This research was carried out in Kotabaru Seberida Village, Keritang Indragiri Hilir District, Riau Province. The selection of informants was carried out by means of a deliberate technique with the number of informants 5 pairs of Javanese and Bugis. The data collection used is observation, interview and documentation study. While the data analysis technique used descriptive analysis according to Miles & Huberman. The data validity verification technique used in this research is the Extension and Triangulation of Participation.               The results showed that communication between Javanese and Bugi ethnic groups in customs is the first thing to do to understand the couple's culture, after gaining an understanding, the next stage is to understand and accept the couple's culture. The process of linguistic acculturation carried out by the Javanese and Bugis couple is verbal and non-verbal communication, the stage is to try to understand the language of the couple so that at the stage using Javanese and Bugis, non-verbal communication is carried out when they don't understand what the tribe of the good couple says. moving their heads or moving their hands only, however, this is not a serious obstacle for Javanese and Bugi couples, they learn from each other to adapt and adapt to their partner's language, although at first they adapt only silently.